Modular invariance and uniqueness of T T ¯ $$ T\overline{T} $$ deformed CFT - Ofer Aharony; Shouvik Datta; Amit Giveon; Yunfeng Jiang; David Kutasov (Journal of High Energy Physics, 2019)
Abstract Any two dimensional quantum field theory that can be consistently defined on a torus is invariant under modular transformations. In this paper we study families of quantum field theories labeled by a dimensionful parameter t, that have the additional property that the energy of a state at finite t is a function only of t and of the energy and momentum of the corresponding state at t = 0, where the theory becomes conformal. We show that under this requirement, the partition sum of the theory at t = 0 uniquely determines the partition sum (and thus the spectrum) of the perturbed theory, to all orders in t, to be that of a T T ¯ $$ T\overline{T} $$ deformed CFT. Non-perturbatively, we find that for one sign of t (for which the energies are real) the partition sum is uniquely determined, while for the other sign we find non-perturbative ambiguities. We characterize these ambiguities and comment on their possible relations to holography.